UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA DIGITAL BERBASIS SUKU ETNIS JAWA PADA MATERI GOTONG ROYONG KELAS IV UPT SPF SDN 101922 BERINGIN - Anggita, Tri Cahya; Yarshal, Dinda; Dwi, Dara Fitrah; Hasibuan, Ahmad Laut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve fourth-grade students’ learning outcomes through digital media based on Javanese ethnic culture on the gotong royong material at UPT SPF SDN 101922 Beringin. The research was motivated by low student learning outcomes caused by the use of conventional teaching methods and less attractive learning media. This study employed a Classroom Action Research (CAR) design conducted in two cycles involving 27 fourth-grade students. Data were collected through observation, tests, and interviews. The digital media were implemented through audiovisual learning media designed using the Canva application, which incorporated Javanese cultural values such as rewang and kerja bakti, reflecting traditional mutual assistance and community service activities in Javanese culture. The results showed a significant improvement in students’ learning outcomes. The average score increased from 70.46 in Cycle I to 85.00 in Cycle II, while classical learning mastery improved from 33.33% to 81.48%. Teacher performance in managing learning activities increased from 72.92% to 89.58%, and student activity improved from 59.09% to 77.27%. Students also became more active, enthusiastic, and cooperative during the learning process. Therefore, digital media based on Javanese ethnic culture proved effective in improving students’ learning outcomes on the gotong royong material.